The impact of family supportive supervisor and co-worker on team cohesion: the mediating role of psychological safety - Pang, Sing Hua (2021)
Based on Newman et al. (2017) proposition on the Integrative Theoretical Framework of Psychological Safety, the current research study investigated Family Supportive Co-worker Behaviour (FSCWB) and Family Supportive Supervisor Behaviour (FSSB) as job resources and their relationships with Psychological Safety and to influence in Team Cohesion as resource investment which is linked to positive work outcomes on Perceived Team Performance, Team Satisfaction and Team Viability. With the increase of resource investment, this would prevent negative work outcomes such as stress and team conflict through resource depletion. In addition, we looked at Psychological Safety as the mediator between FSCWB and Team Cohesion, and also FSSB and Team Cohesion. Our quantitative results supported our hypotheses on FSCWB and FSSB are positively related to Psychological Safety and Team Cohesion as well as Psychological Safety as the mediator for FSCWB, FSSB and Team Cohesion.